The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1093/ecam/nel026
|View full text |Cite
|
Sign up to set email alerts
|

American Ginseng Stimulates Insulin Production and Prevents Apoptosis through Regulation of Uncoupling Protein‐2 in Cultured β Cells

Abstract: American ginseng root displays the ability to achieve glucose homeostasis both experimentally and clinically but the unknown mechanism used by ginseng to achieve its therapeutic effects on diabetes limits its application. Disruption in the insulin secretion of pancreatic β cells is considered the major cause of diabetes. A mitochondrial protein, uncoupling protein-2 (UCP-2) has been found to play a critical role in insulin synthesis and β cell survival. Our preliminary studies found that the extracts of Americ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(55 citation statements)
references
References 39 publications
3
52
0
Order By: Relevance
“…Therefore, reduction or regulation of UCP-2 levels by GA, increased ATP levels and enhanced insulin secretion observed in our study in RINm5F cells is an important observation. Consistent with our study, Luo and Luo (2006) have demonstrated that American Ginseng stimulates insulin production and prevents apoptosis through the regulation of UCP-2 in cultured β-cells.…”
Section: Discussionsupporting
confidence: 93%
“…Therefore, reduction or regulation of UCP-2 levels by GA, increased ATP levels and enhanced insulin secretion observed in our study in RINm5F cells is an important observation. Consistent with our study, Luo and Luo (2006) have demonstrated that American Ginseng stimulates insulin production and prevents apoptosis through the regulation of UCP-2 in cultured β-cells.…”
Section: Discussionsupporting
confidence: 93%
“…This mechanism is related to release of neurotransmitter acetylcholine from nerve terminals in pancreases and stimulation of muscarinic M (3) receptors in β-cells (40;43). Finally, ginseng may prevent β-cell apoptosis (44). This mechanism is related to inhibition of uncoupling protein 2 (UCP2) expression in mitochondria, and an increase in ATP production.…”
Section: Ginseng On β Cellsmentioning
confidence: 99%
“…Some studies have demonstrated that ginseng may enhance glucosestimulated insulin secretion via increasing ATP levels, affecting activity of K ATP channels and Ca 2C channels (Luo & Luo 2006, Park et al 2008a. We discovered that Rb1 significantly increased the ATP:ADP ratio and cytosolic Ca 2C levels in NCI-H716 cells.…”
Section: Discussionmentioning
confidence: 71%